Interparental Conflict and Offspring Marital Satisfaction: The Mediating Role of Communication Patterns - Witami, Adela N; Dannisworo, Cantyo A.; Nurwianti, Fivi; Hanum, Lathifah (Universitas Negeri Padang, 2024)
This study examines how interparental conflict affects offspring's future marital satisfaction, with a focus on the mediating role of communication patterns. A total of 364 married couples participated, using self-report questionnaires and instruments, including the Parental Conflict Intensity/Frequency Scale (PIC-I/F), Spousal Satisfaction Index (CSI-16), and Communication Patterns Questionnaire (CPQ-SF). The results showed that communication patterns did not mediate the relationship between interparental conflict and marital satisfaction. Instead, perceived interparental conflict directly predicted marital satisfaction. These findings highlight the importance of reframing individuals’ perceptions of past parental conflict, rather than just focusing on improving communication skills, to achieve greater marital satisfaction. The study offers valuable insights for family researchers and mental health practitioners in Indonesia, suggesting intervention approaches or therapies to support married individuals from high-conflict families in improving their marital satisfaction.